Application of New Iterative Method to Time Fractional Whitham–Broer–Kaup Equations - Nawaz, Rashid; Kumam, Poom; Farid, Samreen; Shutaywi, Meshal; Shah, Zahir; Deebani, Wejdan (Frontiers in Physics, 2020)
This article presents the Fractional Laplace transform with the help of new iterative method for finding the approximate solutions of coupled system of fractional order partial differential equations. The time fractional Whitham-Broer-Kaup system is taken as test example The fractional derivatives are described in the Caputo sense. Numerical results obtained by the proposed method are compared with that of Adomian Decomposition Method (ADM), Variational Iteration Method (VIM) and Optimal Homotopy Asymptotic Method (OHAM).Numerical results show that the proposed method is reliable and efficient for solution of fractional order coupled system partial differential equations. The accuracy of the method increases by taking higher order approximations.